REGIMES AUTORITÃRIOS EM ÃFRICA: O CASO DA GUINÉ EQUATORIAL - Vaz, Rodrigo (European Scientific Journal, ESJ, 2013)
Authoritarian regimes formed a big part of the African political landscape for several decades since African countries got their independence. With the third wave of democratization, that landscape began to suffer some changes and several authoritarian regimes became hybrid or even democratic ones. However, some countries kept their authoritarian regimes as closed and repressive as before. Equatorial Guinea is one of those cases. This essay aims at, after analysing a wide range of academic literature on authoritarian regimes, understand how – and why – Equatorial Guinea kept the same authoritarian regime, with a transition to an hybrid or even a democratic regime not in sight for the near future.